Extension of sticholysins N-terminal α-helix signals membrane lipids to acquire curvature for toroidal pore formation - Schreier, Shirley; Paulino, Joana; Carretero, Gustavo P B; Barbosa, Leandro R S; Cilli, Eduardo M [UNESP]; Alvarez, Carlos; Ros, Uris (Elsevier, 2024)
Sticholysin I and II (St I/II) belong to the actinoporins family; these proteins form pores in host cell membranes by binding their N-terminal segment to the membrane, leading to protein-lipid (toroidal) pores. Peptides derived from actinoporins pore-forming domains replicate their folding properties and permeabilizing effects. Despite the advances in understanding how these proteins and peptides mediate pore formation, the role of different N-terminal segments in inducing membrane curvature is still unclear. Here we combine circular dichroism, electron paramagnetic resonance, and small-angle X-ray scattering to investigate how synthetic peptides encompassing the N-terminal segments of St I and II (StI1-31, StII1-30, StI12-31, and StII11-30) interact with lipid bilayers and micelles as mimics of the topography of the initial membrane binding and of the subsequently formed positively curved pore. We investigate both the conformational changes and peptides' effects on membrane organization resulting from these interactions. According to the toroidal pore model, our results support that the actinoporins amphipathic α-helices rest at the membrane interface, forming pore walls with lipid head groups, while the 1-10 segment of St II penetrates the bilayer, acting as an anchor. We relate this ability to the higher hydrophobicity of this segment in St II, compared to St I. This unique feature of St II would contribute to enhanced pore formation, explaining St II's increased activity when compared to other actinoporins. Our results reinforce the notion that pore formation by actinoporins is a highly cooperative process where specific protein segments and the lipid bilayer mutually modulate their conformation and organization.